Outpatient clinic waiting time, provider communication styles and satisfaction with healthcare in India. Issue 7 (8th August 2016) - Mehra, Payal
Abstract : Purpose: The research evaluates the impact of extended waiting time on patients' perceptions of provider communication skills and in-clinic satisfaction, in three major cities in India Design/methodology/approach: Design/methodology/approach: 625 patients were interviewed. The multivariate General Linear Model (GLM) was used to determine the causality and relationship between the independent and the dependent variable. A moderation analysis was also conducted to assess waiting time role as a potential moderator in doctor-patient communication. Findings: Results show that patients with higher waiting time were less satisfied with health care quality. Male patients and patients of male providers were more affected by extended waiting time than female patients and patients of female providers. The advanced regression analysis, however, suggests weak support for waiting time and its effect on overall satisfaction with clinic quality. Waiting time did not moderate the relationship between satisfaction with dominant communication style, and overall satisfaction at the outpatient clinic. Research limitations/implications: A cross-sectional study does not easily lend itself to explaining causality with certainty. Thus, sophisticated techniques, such as structural equation modelling may also be utilised to assess the influence of extended waiting time on satisfaction with healthcare at outpatient clinics Practical implications: Findings are relevant for providers as the onus is on them to ensure patient satisfaction. They should initiate a workable waiting time assessment model at the operational level. Originality/value: There has been a relatively lesser focus on patient waiting time in patient-provider satisfaction studies. In India, this aspect is still vastly unexplored especially in the context of outpatient clinics. Gender wise pattern of patient satisfaction and waiting time is also missing in most studies